Reflection and Analysis on Network Maintenance Transition of Telecommunication Operators - Jun Zhu; Bo Zhao; Xiaofeng Wang; Bo Wang (Dianxin kexue)
Newborn things are emerging in an endless stream in recent internet environment, such as VNO（virtual network operation）, OTT（over-the-top）. Maintenance system of telecommunication operators will no longer adapt to internal and external requirements, reflected as revenue growth slowed down, operation and maintenance costs increased and customer perception declined. It was described that in order to improve customer perception and enhance the competitiveness of enterprises, how telecommunication operators worked on network maintenance transition, to realize network maintenance, support business refinement management, improve the capability of rapid response of operation system.